Capacity Development in a Participatory Adaptive Programme: the Case of the Clarissa Consortium - Widmer, Mireille; Apgar, Marina; Afroze, Jiniya; Malla, Sudhir; Healey, Jill; Constant, Sendrine (CLARISSA Research and Evidence Paper, 2022)
Doing development differently rests on deliberate efforts to reflect and learn, not just about what programmes are doing and achieving, but about how they are working. This is particularly important for an action research programme like Child Labour: Action- Research-Innovation in South and South-Eastern Asia (CLARISSA), which is implemented by a consortium of organisations from across the research and development spectrum, during a rapidly changing global pandemic. Harnessing the potential of diverse skills and complementary strengths across partners in responding to the complex challenge of the worst forms of child labour, requires capacity to work together in novel ways. This Research and Evidence Paper documents how CLARISSA approached capacity development, and what we learnt from our challenges and successes. From the start, the programme incorporated a capacity development strategy resting on self-assessment of a wide range of behavioural and technical competencies that were deemed important for programme implementation, formal training activities, and periodic review of progress through an after-action review (AAR) process. An inventory of capacity development activities that took place during the first year of implementation reveals a wide range of additional, unplanned activities, enabled by the programme’s flexibility and adaptive management strategy. These are organised into eight modalities, according to the individual or collective nature of the activity, and its sequencing – namely, whether capacity development happens prior to, during, or after (from) implementation. We conclude with some reflections on the emergent nature of capacity development. Planning capacity development in an adaptive programme provides a scaffolding in terms of time, resources, and legitimacy that sustains adaptiveness. We also recognise the gaps that remain to be addressed, particularly on scaling up individual learning to collective capabilities, and widening the focus from implementation teams to individuals working at consortium level.

Case study: Embedding reform and exiting: LASER’s application of the hourglass approach to achieve sustainable results - Manuel, Clare (DFID-LASER Programme, 2016)
This case study describes how LASER has gone about enabling systemic change and sustainable uptake of reforms that address complex institutional problems in Kenya, Rwanda, Sierra Leone, Somaliland and Uganda. In each of these countries LASER has designed-in a sustainable approach from the start based on: (i) local ownership and leadership of reforms based on developing country (rather than donor) priorities; (ii) use of country (rather than donor programme) systems; and (iii) an understanding that the role of the donor / development practitioner is to support (rather than buy) reform. The case study uses LASER’s hour glass methodology, illustrated with examples from LASER interventions, to show how these principles guide LASER operations every step of the way.
Keywords: IMPORTANT; Practice

How Does the World Bank Build Citizen Engagement Commitments into Project Design? Results from Pilot Assessments in Mozambique, Myanmar, Nigeria, and Pakistan - Nadelman, Rachel; Le, Ha; Sah, Anjali (Working Paper 525, 2019)
How and to what degree is the World Bank putting its new institutional citizen engagement (CE) commitments into practice? This question guides an independent assessment that the Accountability Research Center (ARC) at American University has undertaken as part of the Institute of Development Studies-led Action for Empowerment and Accountability (A4EA) research programme’s investigation into how external actors can best support local processes of and conditions for empowerment and accountability. This report investigates the World Bank’s incorporation of CE into project design, the critical early stage of donor engagement. To accomplish this, ARC reviewed the World Bank’s fiscal year 2015–17 investment project portfolios for four A4EA priority countries, Mozambique, Myanmar, Nigeria, and Pakistan, which covers 57 projects that range from US$19 million to U$600 million. The analysis determines whether projects commit to seeking a strategic approach to CE, which involves combining multiple tactics so that the whole could be greater than the sum of the parts. This assessment of CE commitments is intended to help to inform possible national, civil society organisation strategies to monitor whether and how these commitments are actually implemented in practice.

How to set up and manage an adaptive programme - Lessons from the Action on Climate Today (ACT) Programme - Cooke, Katherine (OPM, 2017)

Seeing the Combined Effects of Aid Programmes - Burge, Richard; Nadelman, Rachel; McGee, Rosie; Fox, Jonathan; Anderson, Colin (IDS Policy Briefing, 2022)
Multiple aid agencies often try to support change in the same places, at the same time, and with similar actors. Surprisingly, their interactions and combined effects are rarely explored. This Policy Briefing describes findings from research conducted on recent aid programmes that overlapped in Mozambique, Nigeria, and Pakistan, and from a webinar with UK Foreign, Commonwealth & Development Office (FCDO) advisors and practitioners. The research found three distinct categories of ‘interaction effects’: synergy, parallel play, and disconnect. We explore how using an ‘interaction effects’ lens in practice could inform aid agency strategies and programming.

Value for money and adaptive programming - Approaches, measures and management - Laws, Ed; Valters, Craig (ODI, 2021)
- The United Kingdom’s Foreign, Commonwealth and Development Office (FCDO)’s standard economy, efficiency, effectiveness/cost-effectiveness and equity (4E) framework is still relevant for approaching, measuring and managing value for money (VfM) for adaptive programmes. • However, this framework needs to be reframed to capture and incentivise flexibility, learning and adaptation. • VfM appraisal and reporting should be done in a way that draws on beneficiary feedback and informs good decision-making, rather than just being a compliance exercise. • If VfM appraisal and reporting cannot be done appropriately for adaptive programmes, it should be avoided or minimised. There is a risk of diverting time and resources from more suitable tools and methods.